Evaluasi Efektivitas Program Berenang Anak Usia Dini Menggunakan CIPP di TK Siloam - Anggelina Pandiangan; Dian Rumahorbo; Elvelina Dwi Glorya Sianturi; Nurhasanah Daulay; Selfi Olivia Siregar; Stephanie Alta Gracia Siregar (Jurnal Pena Pendidikan Dasar, 2026)
This study aims to describe the implementation of the swimming program at Siloam Kindergarten using the CIPP (Context, Input, Process, Product) evaluation model. The study used a survey method with a Likert-scale questionnaire administered to teachers, parents, and the principal. Data were analyzed descriptively to determine trends in respondents' assessments. The results indicate that the swimming program was rated very good across all aspects of the CIPP, including its suitability to children's needs, facility readiness, smooth implementation, and benefits for children's motor development and self-confidence. The swimming program was deemed effective and worthy of being maintained and developed.